Incidence of rheumatoid arthritis at Marjan Teaching Hospital in Babylon, Iraq (2014–2019) - Arwa Hamdan Khudhair Al_Badran; Hussein Chaffat Algabri; Kawther Rafea Hari Al Saeedi; Ali Mohammed Alqazzaz (Medical Journal of Babylon, 2022)
Background: Rheumatoid arthritis is a chronic disease associated with inflammation and progressive damage of joints. It is present in the Middle East and North Africa where the epidemiology of RA remains poorly understood with a dearth of data of the prevalence and activity of disease among Arab countries. The prevalence of RA in Babylon, Iraq in 1975 was 1.02, but during the past decade it was noticed that the prevalence and clinical data varied greatly depending on the area of the study. Objectives: We tried to estimate the incidence of RA in Babylon Province, Iraq during 2014–2019. Materials and Methods: It was a cross-sectional study to detect new cases of the disease in Marjan Teaching Hospital from 2014 to 2019. All patients were diagnosed according to the American College of Rheumatology criteria of 1987 and the revised one of 2010. Results: The total number of new RA cases during this period was 1814 patients. Females were 1577, and male patients were 237. The incidence was 1.1 in 2014 and then reached 1.7 in 2019 with an accumulative risk of 10.0. The average duration of the disease was 2.1 years, and the average age was 43 years. Conclusion: This study was done to follow the previous study performed in the same hospital between 2001 and 2011. The incidence was not significantly increased during the period of this study when compared with other studies. This study lacks the rate of severity and response to treatment, which indicate that another study is needed. It is done to see the incidence of disease and the effect of social and environmental factors that followed war conflicts in the area of Iraq.